Sweet bird of youth = Süßer Vogel Jugend - Williams, Tennessee 1911-1983 (Warner Archive Collection, 2017)
Chance Wayne, an ambitious man craving fame, returns to his southern home with an alcoholic movie star in tow, Alexandra Del Lago. Hoping to capitalize on Del Lago's fame and checkbook, Chance seeks to reunite with his former girlfriend. He finds he is still regarded by others as an unsavory and unwelcome hustler, especially by the father of his ex-girlfriend, a local political boss.